2022
DOI: 10.21203/rs.3.rs-2183545/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide analysis of bHLH57 and functional identification of the involvement of BcbHLH57 in abiotic stress in wucai (Brassica campestris L.)

Abstract: Wucai (Brassica campestris L. ssp. chinensis var. rosularis Tsen), a variety of Brassica cabbage in the Cruciferous family, is a kind of cold-tolerant vegetable widely cultivated in the Jianghuai River Basin of China. To breed new varieties of resistance to stress, it is necessary to study the tolerance of Resistance to different stresses. Transcriptomic data showed that exogenous application of 2, 4-epbrassinolide (EBR) significantly increased bHLH genes in wucai at low temperature, and bHLH57 was up regulate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…found that 2 insertions/deletions (76-bp) in BnFLC-C2 promoter region of Brassica napus were closely related to flowering time. Zhang (2018) found that the point mutation of BcFLC1 gene in WuCai (Brassica campestris L.) could affect its interaction with SVP gene, further affecting the expression of downstream FT and SOC1 genes, resulting in the late bolting phenotype of WuCai (Brassica campestris L.). Cheng (2017) et al summarized 6 pathways regulating flowering time in Arabidopsis thaliana, and pointed out that FCA, FLD, FLK, FPA, FVE, FY and LD were involved in the autonomous flowering pathway, in which the flowering suppressor gene FLC played an important role in the autonomous flowering pathway.…”
Section: Discussionmentioning
confidence: 99%
“…found that 2 insertions/deletions (76-bp) in BnFLC-C2 promoter region of Brassica napus were closely related to flowering time. Zhang (2018) found that the point mutation of BcFLC1 gene in WuCai (Brassica campestris L.) could affect its interaction with SVP gene, further affecting the expression of downstream FT and SOC1 genes, resulting in the late bolting phenotype of WuCai (Brassica campestris L.). Cheng (2017) et al summarized 6 pathways regulating flowering time in Arabidopsis thaliana, and pointed out that FCA, FLD, FLK, FPA, FVE, FY and LD were involved in the autonomous flowering pathway, in which the flowering suppressor gene FLC played an important role in the autonomous flowering pathway.…”
Section: Discussionmentioning
confidence: 99%